Critical reflections on the internationalisation of higher education in the global south - Woldegiorgis, Emnet Tadesse; Yu, Cheryl Qiumei (Diverse perspectives on creating a fairer society, 2024)
Embarking on a journey to Africa, Southeast Asia, South America and beyond, Critical Reflections on the Internationalisation of Higher Education in the Global South explores how postcolonial structures and global power dynamics are shaping the internationalisation of higher education. Challenging the Eurocentric status quo that has long dominated the discourse on internationalisation, this edited collection goes beyond mere discussions of student mobility to address the multifaceted potential that internationalisation holds, ranging from academic partnerships and collaborative research to scholarly publications. Drawing from case studies across the Global South, contributors interrogate not only conventional paradigms, but also pose vital questions. How can institutions in these regions partake equitably in the global exchange of knowledge? What steps can be taken to foster genuine and balanced collaborations between the Global South and North? As a compelling call to action, this research also examines how internationalisation can be a transformative force for the Sustainable Development Goals, breaking down traditional hierarchies and embracing a decolonised future for higher education. If you are involved in academia, policy-making or are simply curious about the complex features of internationalisation in the Global South, this work is your roadmap to deeper, more critical reflections on the internationalisation of higher education.